The Impact of School from Home Implementation on Social-Emotional Development of Early Children in the Era of Covid-19 Pandemic - Elwin Walimatul Fara; Suyadi Suyadi (UPI Kampus Cibiru, 2022)
The Corona Virus (Covid19) is spreading rapidly, so social distancing is imposed to prevent the spread of the virus. This has an impact on teaching and learning activities in schools. So that during the Covid-19 pandemic, the learning system has changed to learning from home (school from home). The change in the learning system to school from home has an impact on various aspects, especially on the achievement of the 5 aspects of early childhood development. The impact of the development of the socio-emotional aspects of children during the implementation of school from home is reviewed in this study. The research methodology uses descriptive qualitative methods with data collection techniques using interviews and observations. This study aims to determine the impact of the implementation of school from home on the socio-emotional development of early childhood in the Karangsoko village environment. The results of interviews and observations state that the implementation of school from home affects children's social behavior, especially for children who have experienced gadget addiction. In addition, children's interest in learning is also reduced and other aspects of development are also reduced.